ANALISIS KOMPREHENSIF PERFORMA SISTEM DAN TINGKAT PENERIMAAN PENGGUNA APLIKASI PERPUSSMULANDU - Nuruddifa Alif Maghfirin; Eddy Kurniawan; Ahmad Farhan (LPPM Universitas Dhyana Pura, 2025)
The utilization of information technology in the education sector plays a crucial role in enhancing the effectiveness of the teaching and learning process. One such implementation is the use of digital libraries, such as the PerpusSMULANDU application developed by SMA Darul Ulum 2 Unggulan BPPT Peterongan. This study aims to analyze the system performance and user acceptance of the PerpusSMULANDU application. The methods used are PIECES (Performance, Information, Economy, Control, Efficiency, Service) to assess system performance, and the Technology Acceptance Model (TAM) to evaluate user acceptance based on perceived ease of use, perceived usefulness, attitude toward usage, behavioral intention, and actual system use. Data were collected through questionnaires distributed to teachers at SMA Darul Ulum 2 Unggulan BPPT Peterongan who use the application. The results show that the application's performance falls into the “satisfactory” category across all PIECES aspects, with the highest score in Information (4.52) and the lowest in Efficiency (4.18). Meanwhile, the TAM analysis shows a high level of user acceptance, with an overall average percentage score of 83.9%, categorized as “very satisfied.” These results indicate that the PerpusSMULANDU application performs well and is well-received by its users. This study is expected to serve as an evaluation and development reference for applications that support digital literacy in the school environment.